Father and daughter, Executive Bachelor of Business Management Graduates, share the stage to celebrate success - Mohammad Syafiq Syahmi, Suhaimi (UMPSA, 2024)
KUANTAN, 29 October 2024 – The 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) witnessed a special moment when a father and his daughter both graduated with an Executive Bachelor of Business Management degree.